Film and Comic Books - McAllister, Matthew P.; Jancovich, Mark; Gordon, Ian, 1954- (Book collections on Project MUSE., 2007)
In Film and Comic Books contributors analyze the problems of adapting one medium to another; the translation of comics aesthetics into film; audience expectations, reception, and reaction to comic book-based films; and the adaptation of films into comics. A wide range of comic/film adaptations are explored, including superheroes (Spider-Man), comic strips (Dick Tracy), realist and autobiographical comics (American Splendor, Ghost World), and photo-montage comics (Mexico's El Santo). Essayists discuss films beginning with the 1978 Superman. That success led filmmakers to adapt a multitude of co.